Ideal Cardiovascular Health, Mortality, and Vascular Events in Elderly Subjects: The Three-City Study - Gaye, Bamba; Canonico, Marianne; Perier, Marie-Cécile; Samieri, Cecilia; Berr, Claudine; Dartigues, Jean-François; Tzourio, Christophe; Elbaz, Alexis; Empana, Jean-Philippe (Journal of the American College of Cardiology, 2017)
The benefit of ideal cardiovascular health (CVH) on health-related outcomes in middle-aged patients is firmly established. In the growing elderly population, the high prevalence of comorbidities and medications for chronic diseases may offset such benefit. This study analyzed the association of ideal CVH with mortality, incident coronary heart disease, and stroke events in elderly individuals from the community. Between 1999 and 2001, 9,294 men and women, noninstitutionalized and aged 65 years and over were examined, and thereafter followed up for the occurrence of vascular events and mortality within the Three-City Study. Hazard ratios (HRs) were estimated by Cox proportional hazard model and compared subjects with 3 to 4 and subjects with 5 to 7 ideal metrics with those with 0 to 2 ideal metrics, respectively. The mean age was 73.8 ± 5.3 years, and 36.7% were men. Only 5% of the participants had ≥5 metrics at the ideal level. After a median follow-up of 10.9 years and 8.6 years, respectively 1,987 deaths and 680 adjudicated coronary heart disease or stroke events had occurred. In multivariate analysis, the risk of mortality and of vascular events decreased across the categories of ideal metrics. In particular, in subjects with ≥5 metrics at the ideal level (compared with those with ≤2), there was a 29% (hazard ratio [HR]: 0.71; 95% confidence interval [CI]: 0.55 to 0.90) decreased risk of all-cause mortality and 67% (HR: 0.33; 95% CI: 0.19 to 0.57) for coronary heart disease and stroke combined (p for trend <0.001). Even in the elderly, higher CVH status is highly beneficial regarding mortality and vascular event risks.